2011
DOI: 10.1108/01409171111146698
|View full text |Cite
|
Sign up to set email alerts
|

A more accurate benchmark for daily electricity demand forecasts

Abstract: PurposeThe purpose of this paper is to propose a simple regression‐based method of forecasting daily electricity demand, which may serve as a more accurate benchmark for short‐term forecasts.Design/methodology/approachIn order to make more efficient use of the calendar effects in electricity demand, including weekend, and seasonal effects, while maintaining the parsimony of the forecasting model, the authors match the demand on each day of an entire year with the average of the corresponding days in recent yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, since they did not improve prediction accuracy (partially due to their lower temporal resolution than our daily prediction), we exclude them from the final specification. Although such economic variables are relevant for longterm forecasts, they do not significantly influence shortterm estimations (Jun and Ergün 2011).…”
Section: Arima Dynamic Harmonic Regressionmentioning
confidence: 99%
“…However, since they did not improve prediction accuracy (partially due to their lower temporal resolution than our daily prediction), we exclude them from the final specification. Although such economic variables are relevant for longterm forecasts, they do not significantly influence shortterm estimations (Jun and Ergün 2011).…”
Section: Arima Dynamic Harmonic Regressionmentioning
confidence: 99%
“…In opinion, the main drawback of this approach consists on how to define the model coefficients search-space limits even though this can be explained by the robustness of the optimization method. Since the majority of forecasting methods concentrate on accuracy, the approach in (Jun and Ergun, 2011) focuses on simplicity. Thus, it can be concluded that it would be better to sacrifice an amount of accuracy to achieve feasibility.…”
Section: Econometric Modelsmentioning
confidence: 99%